Illness perspectives of Thais diagnosed with schizophrenia - Ladda Sanseeha (2018)
This study explored the perceptions of 18 people diagnosed with schizophrenia from 1-10 years to uncover how they perceived themselves and their illness. It also involved 12 family members who added their perceptions. The data were collected using in-depth interviews, reflective journaling, and observations. The data were analyzed through the lens of Heidegger's hermeneutic phenomenology. Four themes emerged: perceptions of mental illness, perceptions of the causes of illness, perceptions of discrimination, and attempting to live with schizophrenia. The findings included strong underlying cultural and spiritual beliefs, and attitudes unique to the Thai participants, including the causation of schizophrenia by supernatural powers, black magic, and bad karma stemming from past deeds. Understanding the perceptions of the participants might help health-care providers to be more sensitive to those living with schizophrenia in Thailand and elsewhere. In particular, the findings could be useful in informing psychiatric careproviders about developing better caring systems for clients diagnosed with schizophrenia. This should help the sufferers of schizophrenia to live their lives to their own satisfaction and as normally as possible. © 2009 The Authors Journal compilation © 2009 Blackwell Publishing Asia Pty Ltd.